The Prevalence and abnormalities of intervertebral discs (ivd) at various levels in lumbosacral spine magnetic resonance imaging (mri): Intervertebral discs (ivd) at various levels in lumbosacral spine magnetic resonance imaging (mri) - Afridi, Abdul Wadood (Medical Journal of South Punjab, 2023)
Abstract Objectives: To use magnetic resonance imaging to identify the prevalence and various abnormalities inside the intervertebral disc at different levels in the lumbosacral spine. Methodology: Cross-sectional study was conducted in the Radiology Department of Hayatabad Medical Complex Peshawar, Pakistan for six months from January 2023 to June 2023. Patients with Intervertebral disc abnormalities were scanned using standard protocol sagittal T1WI, T2WI, T2W STIR, T2W myelo, and in axial T1WI and T2WI. SPSS version 26 was used for data analysis. Tests of significance were applied and a p-value less than or equal to 0.05 was taken as significant. Results: The most frequently affected levels were L4-L5 and L5-S1, with single-site engagement being 30.0% and multi-site involvement being 69.9%. Numbness was 69.9%, Tingling 30.0%, herniated nucleus pulposus 30%, Protrusion 23.5%, Extrusion 6%, Posterolateral 2.7%, Posterocentral 26.2%, Foraminal 3.1%, Canal stenosis (mild 42.2%, moderate 63.2%, severe 5.5%, Thecal sac 36.4%, Lateral recess 55.5%, Foramen 20.1%, Multiple locations 8.3%, Diffuse disc bulge 96.4% (most common on L4-S1), Asymmetric disc bulge 2.4% and Modic changes 21.1% (grade-I 4.2%, grade-II 15.5%, grade-III 1.4%). Ligamentum flavum hypertrophy was at 20.1%, Facet joint hypertrophy at 22%, High-intensity zone (HIZ) at 29.4%, and Annular tear at 26.8% were all abnormalities that were frequently found on the L4-L5 level. Conclusion: Middle-aged persons are at increased risk, females and older individuals showed higher Intervertebral disc abnormalities, and L4-L5 and L5-S1 are the two most afflicted regions. Keywords: [Annular tear, Disc Bulge, High-Intensity zone, Lumbosacral spine, Modic Changes]